A mobile tour guide app for sustainable tourism - Larga, Filipe Eduardo da Silva Vida (2021)
Portugal has had a flourishing tourism sector for the past few years. In fact, Portugal’s tourism boom has made the industry one of the biggest contributors to the national economy and the largest employer. In the year 2019, Portugal had a total of 27 million tourists, surpassing once again the record established in the previous year. However, tourism also brings a series of unintended negative side effects, such as overcrowding. The Santa Maria Maior historic district in Lisbon is being particularly affected by this problem. The work undertaken in this dissertation is part of the Sustainable Tourism Crowding project, that aims to mitigate the overcrowding phenomenon in this district, by fostering a balanced distribution of visitors while promoting the visitation of sustainable points of interest. This dissertation focuses on developing a mobile app prototype targeted at tourists, through which these sustainable walking tour recommendations can be delivered. To validate the functional requirements of the prototype, more specifically the trip creation process, a series of unit tests, integration tests, and manual tests were developed. To evaluate the usability of the prototype, a user-centered approach was adopted during the design stage, in which two usability techniques were conducted with members of ISCTE’s research center ISTAR and partners from the Junta de Freguesia de Santa Maria Maior, that guided and validated the decisions made. The achieved prototype contains mechanisms for measuring tourists’ adherence to the recommended tours using the Dynamic Time Warping algorithm, which raises new research opportunities on tourists’ behaviour.